A Review on Analytical and Pharmacological Description of Ornidazole - Kant Gupta, Krishan; Bhardwaj, Abhay; Pathak, Anuj; Raghavendra Rao, N.G.; Prakash, Surya (Journal of Neonatal Surgery, 2025)
Ornidazole is a well-known Anti-bacterial drug associated with the Nitroimidazole class. It’s a class II BCS compound with poor solubility in inorganic solvents. Hoffmann-La-Roche synthesized orinidazole in 1966. Anaerobic bacteria are susceptible to the antibacterial and antiprotozoal effect of ornidazole. This review mainly focuses on various analytical estimations techniques of ornidazole and compares it with other drug compounds. This is a comprehensive review of previous research on the drug ornidazole